Enhanced decolorization efficiency of acid orange 7 by electric field granular-activated carbon combined system and its statistical optimization by response surface methodology - Jung, Kyung-Won; Park, Dae-Sun; Ahn, Kyu-Hong (WILEY, 2015)
In this study, the decolorization of Acid Orange 7 AO-7), a model pollutant, was experimentally investigated by combining granular-activated carbon GAC) in an electrochemical treatment system, which in this investigation is called an EF-GACC Electric Field and Granular Activated CarbonCombined) system. The results of preliminary testing showed that the EF-GACC system exhibited a greatly higher decolorization performance for AO-7 than did either the individual electric field or GAC adsorption system. This is mainly due to the dual action of GAC in the system as adsorbent and moving conductor. Subsequently, to statistically optimize the key parameters applied voltage, GAC concentration, initial pH, and reaction time) in the EF-GACC system and thereby maximize the decolorization efficiency, a response surface methodology with a Box-Behnken design was used. In terms of the results, the overall performance revealed that the decolorization was well fitted by a quadratic regression model developed in this study and that the selected independent variables had significant interactive effect on the decolorization efficiency. Through numerical optimization, the complete decolorization and destruction of the parent molecule were obtained under statistically optimized conditions: an applied voltage of 28 V, a GAC concentration of 30 g/ L, an initial pH of 5.0, and a reaction time of 40 min. The scaleup and semicontinuous sequencing batch reactor system was satisfactorily tested and found to have an average decolorization of 99.7% 60.3%. (c) 2015 American Institute of Chemical Engineers Environ Prog, 34: 1674-1682, 2015
Keywords: 3-PHASE 3-DIMENSIONAL ELECTRODE; WASTE-WATER TREATMENT; ELECTROCHEMICAL TREATMENT; FERMENTATIVE HYDROGEN; AQUEOUS-SOLUTIONS; REACTIVE BLACK-5; DYE; DISINFECTION; PERFORMANCE; ADSORPTION